Faktor pembentuk niat perilaku penggunaan dompet digital pada aplikasi marketplace - Shellen Shellen; Margaretha Ardhanari; Deatri Arumsari Agung (Jurnal Manajemen Maranatha, 2023)
Peoples preferences for shopping online and paying with digital wallets have shifted since the COVID-19 pandemic. Nonetheless, there is still inadequate research focusing on the use of digital wallets in shopping transactions on Indonesian marketplace platforms. The purpose of this study is to investigate and assess the impact of performance expectancy, effort expectancy, self-efficacy, social influence, attitudes, and perceived behavioral control on behavioral intentions in Indonesians who use digital wallets. This is a quantitative study that employs purposive sampling approaches to determine respondents. Data was collected by the distribution of online questionnaires to a total of 170 respondents. The PLS-SEM (Partial Least Square - Structural Equation Modeling) data analysis technique was employed in this study, along with Smart-PLS software. Hypothesis testing results reveal that performance and effort expectancies influence attitudes. Furthermore, it has been demonstrated that self-efficacy influences perceived behavioral control. Attitudes and perceived behavioral control have also been proven to influence behavioral intentions positively. The managerial implications of this research center on the strategy of marketplace platforms in increasing the use of digital wallets in Indonesia. The novelty of this research can be found in the role of self-efficacy, perceived behavioral control, and social influence on behavioral intentions, which has not been widely studied in Indonesia. This research also focuses on using digital wallets in Indonesia, which represents a wide opportunity for online retailers.